2006
DOI: 10.1007/s00268-005-0374-5
|View full text |Cite
|
Sign up to set email alerts
|

A Prophylactic Infusion of Calcium Solution Reduces the Risk of Symptomatic Hypocalcemia in Patients after Total Thyroidectomy

Abstract: A prophylactic infusion of calcium solution after total thyroidectomy may be useful in reducing the development of symptomatic hypocalcemia and reduces the patients' risk of having discomfort and anxiety due to hypocalcemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 22 publications
2
23
0
4
Order By: Relevance
“…Although a single functioning parathyroid is reported to be sufficient for maintenance of calcium balance, publications stating that at least two of the glands should be removed to result in temporary or permanent hypoparathyroidism due to incidental parathyroidectomy are also present (16,29,30). In our study, the rate of incidental parathyroidectomy was found to be 10.5%.…”
Section: Discussionsupporting
confidence: 51%
“…Although a single functioning parathyroid is reported to be sufficient for maintenance of calcium balance, publications stating that at least two of the glands should be removed to result in temporary or permanent hypoparathyroidism due to incidental parathyroidectomy are also present (16,29,30). In our study, the rate of incidental parathyroidectomy was found to be 10.5%.…”
Section: Discussionsupporting
confidence: 51%
“…In 40-50% of such cases, it has been found that the parathyroid gland was located within the thyroid gland (12). It is usually reported that at least two glands should be injured for hypoparathyroidism to develop (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…6 In a study by Uruno et al, calcium solution infusion was found to be beneficial in preventing the development of symptomatic hypocalcaemia thereby reducing patient distress,however no patients required intravenous calcium for symptomatic hypocalcaemia in the present study. 7 Oral administration of 1 µg of calcitriol twice per day and 500 mg of calcium salts 3 times per day after total thyroidectomy significantly decreased the risk of severe postoperative hypocalcemia. 8 These studies suggest that post thyroidectomy hypocalcaemia can be considerably prevented by the routine prophylactic administration of calcium and vitamin D supplements.…”
Section: Discussionmentioning
confidence: 99%